Exploring English Reading Barriers: A Teacher’s Perspective from a Remote Elementary School - Jessica Angeline De Eloisa Tobing; Dedi Dedi; Harmita sari (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2026)
Reading instruction in English at the elementary school level plays a crucial role in academic development, particularly for students in remote areas. This study aims to explore the reading challenges faced by students learning English at a remote elementary school in Taiwan, based on the perspectives of the foreign English teacher (FET). The focus of this research is to identify the barriers affecting students' reading abilities and to find teaching strategies that can overcome these challenges. This study employs a qualitative descriptive approach, with the subjects being English teachers at an elementary school in a remote area. Data were collected through semi-structured interviews with a foreign English teacher (FET) and analyzed using the data condensation, data display, and conclusion verification methods.  The results indicate that key challenges include low motivation, limited vocabulary, first language interference, curriculum gaps, and limited exposure to native English contexts. Beyond identifying barriers, this study contributes to the field of TEFL in under-resourced areas by proposing a localized pedagogical framework that aligns curriculum expectations with students' developmental readiness. It offers significant implications for policymakers regarding the necessity of early-grade exposure and provides educators with evidence-based strategies to bridge the home-school disconnect through enhanced family engagement and structured phonetic instruction.